Fighting Staphylococcus epidermidis Biofilm-Associated Infections: Can Iron Be the Key to Success? - Oliveira, Fernando; Rohde, Holger; Vilanova, Manuel; Cerca, Nuno (Frontiers in Cellular and Infection Microbiology, 2021)
Staphylococcus epidermidis is one of the most important commensal microorganisms of human skin and mucosae. However, this bacterial species is also the cause of severe infections in immunocompromised patients, specially associated with the utilization of indwelling medical devices, that often serve as a scaffold for biofilm formation. S. epidermidis strains are often multidrug resistant and its association with biofilm formation makes these infections hard to treat. Their remarkable ability to form biofilms is widely regarded as its major pathogenic determinant. Although a significant amount of knowledge on its biofilm formation mechanisms has been achieved, we still do not understand how the species survives when exposed to the host harsh environment during invasion. A previous RNA-seq study highlighted that iron-metabolism associated genes were the most up-regulated bacterial genes upon contact with human blood, which suggested that iron acquisition plays an important role in S. epidermidis biofilm development and escape from the host innate immune system. In this perspective article, we review the available literature on the role of iron metabolism on S. epidermidis pathogenesis and propose that exploiting its dependence on iron could be pursued as a viable therapeutic alternative.